2007
DOI: 10.1590/s0074-02762007000700018
|View full text |Cite
|
Sign up to set email alerts
|

First record of molluscs naturally infected with Angiostrongylus cantonensis (Chen, 1935) (Nematoda: Metastrongylidae) in Brazil

Abstract: Seeking the identification ofA. cantonensis has already been found in Southeast Asia, South Pacific, Africa, India, Caribbean, Australia, North America (Pien & Pien 1999), Jamaica (Lindo et al. 2002) and Haiti (Raccurt et al. 2003).Eosinophilic meningitis is a rare clinical entity that is defined by the presence of 10 or more eosinophils/ ml in the cerebrospinal fluid (CSF) or a CSF eosinophilia of at least 10% of the total CSF leukocyte count (Kuberski 1979). The most common cause is invasion of the central n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
107
0
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(130 citation statements)
references
References 14 publications
(16 reference statements)
1
107
0
11
Order By: Relevance
“…Cerebral angiostrongyliasis has been reported in Southeast Asia, Africa, Australia, America (Wang et al 2008), and recently transmission foci have been identified in Brazil (Caldeira et al 2007;Maldonado et al 2010) and Ecuador (Pincay et al 2009). In addition, angiostrongyliasis is considered an emerging public health problem in the United States (Diaz, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral angiostrongyliasis has been reported in Southeast Asia, Africa, Australia, America (Wang et al 2008), and recently transmission foci have been identified in Brazil (Caldeira et al 2007;Maldonado et al 2010) and Ecuador (Pincay et al 2009). In addition, angiostrongyliasis is considered an emerging public health problem in the United States (Diaz, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the state of São Paulo, the geographical distribution of A. fulica is widened from 69 counties 17 A. fulica has been found in Brazil (Espírito Santo and São Paulo), infested by larvae of Metastrongyloidea A. cantonensis 1,2 . In the state of Santa Catarina (City of Florianópolis), 244 specimens of A. fulica were collected, which were imposed to experimental infection by A. costaricensis larvae 8 .…”
Section: Resultsmentioning
confidence: 99%
“…These data are especially useful and can be used by public health authorities to establish policies related to surveillance and planning of preventive actions. Isolated cases of eosinophilic meningoencephalitis have recently been reported in Brazil 9,11,14,15,46,47 . Thus, it is plausible that A. cantonensis continues to spread to new regions, increasing the risk of eosinophilic meningoencephalitis in humans.…”
Section: Several Snails Play Roles As Intermediate Hosts Formentioning
confidence: 99%
“…A. cantonensis has been observed in several regions of the world [3][4][5][6][7] , and they were distributed from Eastern Asia to other continents by two main hosts: rats (definitive hosts) and Achatina fulica Bowdich, 1822 (one of the intermediate hosts), especially during the Second World War 8 . Several species of land and freshwater snails have also been found to be naturally infected with A. cantonensis [9][10][11][12][13][14] . In Brazil, the occurrence of A. cantonensis has been reported in all states except for Acre [9][10][11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation